Relapsing polychondritis following PD-1 blockade diagnosed via 18F-FDG PET/CT and improved by steroid administration: a case report and literature review - Xu, Ruo-Wen; Dong, Wen-Bo; Wang, Yong-Xu; Liu, Yong-Qi; Chen, Chen; Wang, Wei; Liu, Hai-Na; Jin, Hong-Yu; Li, Wen-Yang (Frontiers in Immunology, 2025)
BackgroundUp to 22% of cancer patients treated with immune checkpoint inhibitors (ICIs) can experience immune-related adverse events (irAEs) that mimic rheumatic disease, such as relapsing polychondritis (RP), which is a rare autoimmune disease that mainly manifests as inflammation of airway cartilage.MethodsWe report a case of RP induced by humanized recombinant anti-PD-1 monoclonal antibody therapy (tislelizumab). 18F-Fluorodeoxyglucose positron emission tomography/ computed tomography (18F-FDG PET/CT) contributed to the diagnosis of RP, and methylprednisolone was used to effectively control its progression. We also reviewed 13 publications on drug-induced RP in the context of cancer and analyzed the pathogenesis, ancillary tests, treatment, and prognosis of the cases described therein. ResultsIncluding our case, 14 drug-related RP cases with a tumor background were analyzed. Patients usually develop related symptoms 3–5 months after initiating medication. The primary tumor involvement sites included the hematological system (5/14, 35.71%), upper digestive tract (4/14, 28.57%), skin (2/14, 14.29%), reproductive system (2/14, 14.29%), bone (1/14,7.14%), and lung (1/ 14, 7.14%). Conclusion18F-FDG PET/CT plays a crucial role in diagnosing RP caused by PD-1 monoclonal antibodies. Early detection and the prompt administration of corticosteroids are crucial in effectively controlling the progression of RP, helping to alleviate symptoms and prevent further complications.